Solusi Persamaan Panas Dimensi Satu dengan Metode Transformasi Laplace dan Transformasi Elzaki - Zaki, Ahmad; Syam, Rahmat; Lubis, Kristina (Jurusan Matematika FMIPA UNM, 2022)
This study aims to determine the solution to the one dimensional heat equation using the Laplace transformation and Elzaki transformation. This research is a pure research that examines the Laplace transformation and Elzaki transformation in the one dimensional heat equation